Sleep and brain function - Urade, Yoshihiro; Mohri, Ikuko (No to hattatsu, 2006)
Lipocalin-type prostaglandin (PG) D synthase (L-PGDS) catalyzes the isomerization of PGH2, a common precursor of various prostanoids, to produce PGD2, a potent endogenous somnogen. L-PGDS is localized in the leptomeninges, choroid plexus, and oligodendrocytes of the central nervous system. PGD2 is proposed to be a major humoral sleep-inducing factor accumulated in the brain during wakefulness. PGD2 stimulates DP, receptors localized in the basal forebrain and increases the local extracellular concentration of adenosine, which activates A2A receptor-possessing neurons in the basal forebrain and/or ventrolateral preoptic area (VLPO). The intracerebroventricular infusion of PGD2 or adenosine A2A receptor-agonists induces non-REM sleep and increases the expression of fos protein in VLPO. The activation of VLPO neurons is associated with decreased fos expression in the histaminergic tuberomammillary nucleus (TMN), one of the arousal centers. The GABAergic inhibition of TMN is involved in non-REM sleep induction by PGD2 or adenosine A2A receptor-agonists. The neural network between VLPO and TMN is considered to play a key role in the regulation of vigilance states.